Optimization of the heterogeneous vehicle routing problem with cross docking logistic system - Nader Al Theeb; Omar Al-Araidah; Manar H. Aljarrah (Logistics Research, 2019)
This paper introduces a new mixed integer model to provide efficient distribution plans to route a set of inbound/outbound heterogeneous vehicles in the crossdocking systems that are used to transfer different types of commodities from a manufacturing plant to retail warehouses with allowed split deliveries. The objectives are to minimize the total commodity deviations and the overall distribution time or cost of vehicles. Different data sets from different scales are randomly generated and solved by CPLEX-Concert Technology. As the proposed model is NP-hard; a new heuristic is constructed to solve the problem in reasonable computational efforts. Results show that CPLEX can obtain optimal solutions for small-scale sets and sub-optimal solutions for medium scale sets with a six-hour time limit, while it fails to provide any feasible solution for 35 out of 50 large scale sets. The proposed heuristic provides very competitive results compared to CPLEX in all scales in term of gaps and computational times.
Keywords: 650; Logistics; Cross dock; Vehicle routing; Integer programming; Heuristic